Social representations of the natural disaster (February 6 earthquake) A field study in Latakia city)) (Journal of Hama University, 2025)
The current research aims to identify the social representations of the natural disaster (February 6 earthquake) among a sample of families affected by the February 6 earthquake in Latakia city. The sample consisted of 7 families that included (20) individuals. The sample was drawn randomly using the Vergès serial recall technique in (1992). The results showed that the perceptions were mostly negative and the central nucleus consisted of the word (fear) and the primary peripheral device consisted of (fatigue, insecurity, despair, terror). The contrast area contained the words (instability, submission to fate, loss, loss). The secondary peripheral device consisted of (appreciation of blessing, hope, clinging to life). As for the parents’ perceptions, the words (fear, fatigue) formed the central nucleus of the social perception of the natural disaster, as they are the most frequently repeated and important words and therefore the most stable among the parents of the sample members. As for the primary peripheral elements,  It includes the words (responsibility, shock), as for the contrasting elements, it includes the words (insecurity, despair, disaster, anxiety, panic, sadness, instability, loss), as for the secondary peripheral elements of the concept, it contains the words (terror, sadness, instability, loss, lack of independence, loss, tragedy, submission to fate and destiny.